Identification, Expression Patterns and RNA Interference of Aquaporins in Dendroctonus armandi (Coleoptera: Scolytinae) Larvae During Overwintering - Fu, Danyang; Dai, Lulu; Gao, Haiming; Sun, Yaya; Liu, Bin; Chen, Hui (Frontiers in Physiology, 2019)
The ability to survive annual temperature minima could be a key determinant of distribution limits for insect under global climate change. Recent studies have suggested that insect aquaporins are indispensable for cellular water management under conditions that lead to dehydration and cold stress. Aquaporins are integral membrane water channel proteins in the major intrinsic protein superfamily and promote selected solutes and the movement of water across biological membranes. We cloned and characterized nine full-length aquaporins from Dendroctonus armandi (DaAqps), the most destructive forest pest in the Qinling Mountains of Shaanxi Province, China. Eight of the DaAqps belong to three classical aquaporin grades, including the Drosophila integral protein, the Pyrocoelia rufa integral protein, the entomoglyceroporins and one that belongs to the unorthodox grade of aquaporin 12-like channels. The DaAqps were multiply expressed during different developmental stages and in different larval tissues, and expression peaked in mid-winter. They were tested under cold conditions for different lengths of time, and the expression of almost DaAqps was down-regulated with decreasing temperature and long-term exposure to cold conditions. However, when the lowest temperatures were reached, the levels were immediately up-regulated. These genes indicate that could improve cold-tolerance through mortality responses at low temperature after RNA interference of DaAqps. In our study, we analyzed the molecular response, expression patterns, and RNA interference of DaAqps and clariﬁed the crucial role of protective compounds (aquaporins) underlying D. armandi cold tolerance and could provide a new pest control method.